Among Early Appearing Non-Motor Signs of Parkinson’s Disease, Alteration of Olfaction but Not Electroencephalographic Spectrum Correlates with Motor Function - Cozac, Vitalii V.; Auschra, Bianca; Chaturvedi, Menorca; Gschwandtner, Ute; Hatz, Florian; Meyer, Antonia; Welge-Lüssen, Antje; Fuhr, Peter (Frontiers in Neurology, 2017)
Olfactory decline is a frequent and early non-motor symptom in Parkinson’s disease (PD) which is increasingly used for diagnostic purposes. Another early appearing sign of PD consists in EEG alterations. The combination of olfactory and EEG assessment may improve the identification of patients with early stages of PD. We hypothesized that olfactory capacity would be correlated with EEG alterations and motor and cognitive impairment in PD patients. To our knowledge, the mutual influence of both markers of PD – olfactory decrease and EEG changes – was not studied before. We assessed the function of odor identification using olfactory «Screening 12 Test» («Sniffin’ Sticks®»), between two samples: patients with PD and healthy controls (HC). We analyzed correlation between the olfactory function and demographical parameters, UPDRS-III, cognitive task performance and spectral alpha/theta ratio (α/θ). Additionally, we used ROC-curve analysis to check the classification capacity (PD vs HC) of olfactory function, α/θ, and a combined marker (olfaction and α/θ). Olfactory capacity was significantly decreased in PD patients, and correlated with age, disease duration, UPDRS-III, and with items of UPDRS-III related to gait and axial rigidity. In HC olfaction correlated with age only. No correlation with α/θ was identified in both samples. Combined marker showed the largest Area under the curve. In addition to EEG, the assessment of olfactory function may be a useful tool in the early characterization and follow-up of PD.